Starlikeness Associated with Tangent Hyperbolic Function. (20th May 2022) - Tang, Huo; Arif, Muhammad; Ullah, Khalil; Khan, Nazar; Haq, Mirajul; Khan, Bilal
Abstract : The primary objective of this study is to establish a class of starlike functions (symmetric under rotation) that are related to a tangent hyperbolic. Integral preserving properties along with the sufficiency criteria involving coefficients are investigated for the same class. Differential subordinations problems, which are linked to Janowski and tangent hyperbolic functions, are also discussed. We also utilize these findings to find sufficient conditions for the starlike functions.